EDUCATION OF STUDENTS IN SPECIAL BOARDING SCHOOLS THROUGH INTERACTIVE METHODS (International journal of artificial intelligence, 2024)
The article discusses the use of the scamper method in the effective organization of technology classes in specialized schools and boarding schools for children with disabilities.